ЧИСЕЛЬНЕ ДОСЛІДЖЕННЯ ЕЛЕКТРИЧНОГО ПОЛЯ У ВИСОКОВОЛЬТНІЙ КАБЕЛЬНІЙ МУФТІ З КОНУСОМ ВИРІВНЮВАННЯ ПОЛЯ - Кучерява, І.М. (Інститут електродинаміки НАН України, Київ, 2017)
The electric field distribution in the vicinity of stress cone of high-voltage XLPE insulated cable termination (110 kV) is studied by computer modeling. The dependence of cable insulation conductivity on electric intensity and the different cone positions relative to the cutting ends of the cable outer semiconducting layer and copper wire shield are taken into account. The stress control cone is considered both in the form of only cone reflector and as a complete stress cone with insulation body. The peculiarities of field distribution depending on the cone shape and surface roughness are analyzed. The attained results are of interest for designing and improvement of up-to-date high- and extra- high-voltage cable terminations. References 13, figures 5, table 1.